Comprehensive sequencing of the LRRK2 gene in patients with familial Parkinson's disease from North Africa - Jasinska-Myga, Barbara; Kachergus, Jennifer; Vilariño-Güell, Carles; Wider, Christian; Soto-Ortolaza, Alexandra I.; Kefi, Mounir; Middleton, Lefkos T.; Ishihara-Paul, Lianna; Gibson, Rachel A.; Amouri, Rim; Yahmed, Samia Ben; Sassi, Samia Ben; et al. (Movement disorders, 2010)
The LRRK2 gene is a key player in Parkinson's disease (PD), however prevalence and pathogenicity of LRRK2 variants remain to be investigated in ethnically diverse populations. Herein, we performed comprehensive sequencing of the LRRK2 gene in 92 Tunisian probands with familial PD. We then performed an association study using all identified variants in a series of 167 Lrrk2 p.G2019S‐negative patients with sporadic PD and 365 Lrrk2 p.G2019S‐negative healthy control subjects, all from the same Arab‐Berber ethnicity. We identified one novel coding substitution (p.M2408I) and 24 known coding changes. Only the Lrrk2 p.G2019S mutation segregated with disease within families and was found in 39% of familial probands. None of the variants displayed significant association with risk for sporadic PD, however a trend was observed for Lrrk2 p.Y2189C. The present study underscores the importance of the LRRK2 gene in the Tunisian PD population. © 2010 Movement Disorder Society